Making milk with conscious care: Raw milk ontologies and the practices of 'bath milk' producers in Victoria, Australia. (January 2019) - Linn, Alanna
Abstract: The sale of raw cow milk for human consumption is banned in Australia due to regulatory requirements that all milk must be pasteurised for safety reasons. However, some dairy farmers produce raw milk for sale as 'bath milk', a product labelled 'for cosmetic purposes only' but which is often bought for drinking. This situation is mirrored in other countries where raw milk is banned, and it is highly contentious, yet while there is significant literature examining why people drink raw milk, there has been little analysis exploring the views and practices of these farmers. Drawing notably on the theoretical work of Annemarie Mol and John Law around ontological multiplicity, this paper explores the accounts of a number of such farmers in Victoria, Australia. It finds that these farmers explicitly rejected the normative definition of raw milk as inherently dangerous, along with the associated regulatory framework. Instead, they developed their own structured practices that were designed to produce a version of raw milk that could be drunk, but which existed outside of the food regulation system. This situation highlights how practices can enact different versions of a food and, at the same time, the challenge for food safety regulation in being able to engage with, and account for, alternative and more complex versions of food and risk. Highlights: Production of bath milk occurs in a number of countries where raw drinking milk is prohibited. Accounts of bath milk producers, who reject the definition of raw milk as inherently dangerous, are underexplored. .These producers have developed their own structured practices to produce an alternative versions of raw milk and risk. .Food safety regulation has been unable to engage with such alternative, and more complex, versions of food and risk.